An Analysis of the European Union (EU) Multilateral Foreign Policy Towards Zimbabwe 2000-2008 - Percyslage Chigora (Elsevier, 2022)
Zimbabwe at the turn of the new Millennium has received widespread condemnation from the European Union (EU), particularly following the abandonment of the Structural Adjustment Programmes, intervention in the Democratic Republic of Congo and with the implementation of the controversial land reform programme. The image portrayed by the EU has been based reports of violence, instability and abandonment of the rule of law, which has created a serious challenge to modern developments on democracy and human rights. This was followed by the EU’s imposition of sanctions on Zimbabwe and denigrating policies and events organized and formulated by the Zimbabwean government. From such a standpoint the paper seeks to examine and analyse the historicity and causes of this strain in relations between Zimbabwe and EU. It will also analyse the extent to which Zimbabwe and the EU as actors in the international system have been affected. Finally, the paper will offer an analysis into the future of Zimbabwe in its interaction with the EU.